The Utilization of Aluminum Sulfate Doses with Jar Test at Local Water Treatment Company in Jambi CitJ - Corry Handayani; Novi Indrawaty; Novrianti Novrianti (Universitas Ahmad Dahlan, 2023)
Surface water before being used for certain purposes should be treated by special treatment. This process such kinds of procedure reducing the turbidity, color, and bacteria effect on the water. A kind of attention to the source water is cultivating the water by installing water treatment for the sake of the water that is produced is proper to be consumed and distributed to the society. The local company that does this kind of treatment in Jambi city is the local drinking water company, Tirta Mayang. By using the coagulant, aluminum sulfate, at the treatment processing, this company cultivates the source water from the Batanghari river. Three factors determine the success of the coagulant that is used, listed various chemicals, doses of chemicals, and the mixture of chemicals that are used. By using the jar test, this research yielded that the utilization of aluminum sulfate in the dry season is more than in the rainy season.